THE GROWTH OF “PISANG RAJA BULU” PLANLETS IN THE LIGHTING OF INCUBATION ROOMS AND GROWTH REGULATOR AGENTS OF BROWNING PREVENTION BY IN VITRO - Utami Setyawati; Ari Wijayani; Endah Wahyurini (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
The aims of this research were to determine the lighting of incubation rooms and browning prevention agents on the growth of “Pisang Raja Bulu” planlets by in vitro and determine whether there is a best interaction between the incubation rooms lighting and the type of browning prevention agents in the growth of “Pisang Raja Bulu” planlets that plants in vitro. This research was conducted in the Biotechnology laboratory of the Faculty of Agriculture, UPN